2015
DOI: 10.1002/chem.201502968
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Use of Gold(I) Complexes Containing a Hemilabile Phosphanylferrocene Nitrile Donor

Abstract: Removal of the chloride ligand from [AuCl(1-κP)] (2) containing a P-monodentate 1'-(diphenylphosphanyl)-1-cyanoferrocene ligand (1), by using silver(I) salts affords cationic complexes of the type [Au(1)]X, which exist either as cyclic dimers [Au(1)]2 X2 (3 a, X=SbF6 ; 3 c, X=NTf2 ) or linear coordination polymers [Au(1)]n Xn (3 a', X=SbF6 ; 3 b', X=ClO4 ), depending on anion X and the isolation procedure. As demonstrated for 3 a', the polymers can be readily cleaved by the addition of donors, such as Cl(-) , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 91 publications
(43 reference statements)
1
29
0
Order By: Relevance
“…Yield 73 mg, 81%. 31 General procedure of AgXP 3 (X = Cl, Br, I) complexes (14)(15)(16) AgPF 6 (25.3 mg, 0.1 mmol) was dissolved in acetone (5 ml) and a solution of the corresponding tetrabutyl ammonium halide NBu 4 X (0.1 mmol) in dichloromethane (10 ml) was added. The suspension was stirred for 10 min in the absence of light.…”
Section: General Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yield 73 mg, 81%. 31 General procedure of AgXP 3 (X = Cl, Br, I) complexes (14)(15)(16) AgPF 6 (25.3 mg, 0.1 mmol) was dissolved in acetone (5 ml) and a solution of the corresponding tetrabutyl ammonium halide NBu 4 X (0.1 mmol) in dichloromethane (10 ml) was added. The suspension was stirred for 10 min in the absence of light.…”
Section: General Commentsmentioning
confidence: 99%
“…AgClP 3 (14). Colorless crystalline material (57.2 mg, 74% (16). Colorless crystalline material (73.7 mg, 85.0%).…”
Section: General Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These functionalized ferrocene derivatives and their metal complexes represent an important topic of research in many fields such as organic synthesis, catalysis, asymmetric catalysis, materials chemistry, and in medicine as antimalarial or antitumor agents. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In particular, ferrocenyl phosphines have been studied thoroughly, as represented by the well-known 1,1′-bis(diphenylphosphino)ferrocene (dppf ). [1] Some of us have described the formation of several amidephosphines containing ferrocene units, studied their coordination chemistry, [17,18] and also showed that some gold and silver complexes are active as antitumor agents.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic ring closing of (Z)-3-methylpent-2-en-4-yn-1-ol was examined using 1ʹ-(diphenylphosphino)-1-cyanoferrocene gold chloride [(C5H4CN)Fe(C5H4PPh2AuCl)] as the catalyst. [20] Ring closing was accomplished in 65% conversion when [(C5H4CN)Fe(C5H4PPh2AuCl)] was used as the catalyst and rose to >97% when the chloride ligand of [(C5H4CN)Fe(C5H4PPh2AuCl)] was abstracted with a silver salt.…”
Section: Introductionmentioning
confidence: 99%